2013
DOI: 10.1039/c3em30737a
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of antiandrogenic activity in gray water and domestic wastewater treated by the MBR process

Abstract: In order to figure out the variation of the androgens/antiandrogens in wastewater treatment, androgenic/antiandrogenic activities were investigated in two membrane bioreactors (MBR) treating gray water and domestic wastewater, respectively, in Beijing city, China. The androgens and antiandrogens were extracted from water and solid samples by a solid phase extraction (SPE) method and the androgenic/antiandrogenic activities were detected with a recombined androgen receptor (AR) yeast assay. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Pretreatment was conducted according to the previous study with proper modification (Ma et al, 2013). In order to suppress possible biotic activity, an appropriate amount of methanol (2 mL/L) was added to each sample right after the sampling.…”
Section: Samples Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment was conducted according to the previous study with proper modification (Ma et al, 2013). In order to suppress possible biotic activity, an appropriate amount of methanol (2 mL/L) was added to each sample right after the sampling.…”
Section: Samples Pretreatmentmentioning
confidence: 99%
“…Some antiandrogens, e.g., triclosan, 4-nonylphenol, bisphenol A, octocrylene, butylparaben, propylparaben, benzophenone-3, and 3,4-dichlorophenol, were found in gray wastewater (Leal et al, 2010). We had previously reported the occurrence and removal of antiandrogenic activity of gray wastewater in a MBR treatment system (Ma et al, 2013). Nevertheless, further research is still needed on the specific properties of antiandrogens in gray wastewater and their removal in the treatment system.…”
Section: Introductionmentioning
confidence: 99%
“…Antiandrogenic activity of 935 mg flutamide equivalent concentration (FEQ)/L has been detected in the surface water in China (Zhao et al, 2011). A recent study reported that more than 1800 mg FEQ/ L anti-androgens flow into the graywater every day in Beijing (China) (Ma et al, 2013). In vitro anti-androgenic activity (370-4223 mg FEQ/L) has also been determined in the freshwater in Italy (Urbatzka et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The anti-androgenic nature of phthalates is also uncertain in fish because they have been reported to displace 17β-estradiol (E2) from the ERs in rainbow trout (Oncorhynchus mykiss) (Matthews et al, 2000), thereby, suggesting an in vivo estrogenic MoA. The detection of anti-androgenic activity in water worldwide (Jobling et al, 2009;Jolly et al, 2009;Ma et al, 2013;Urbatzka et al, 2007) and foreseeing the importance of androgens in the process of oocyte maturation in fish such as yellow croaker (Larimichthys crocea), European sea bass (Dicentrarchus labrax), Japanese eel (Anguilla japonica) and Atlantic cod (Gadus morhua) (Endo et al, 2011;Garcia-Lopez et al, 2011;Kortner et al, 2009;Pu et al, 2013), have necessitated the evaluation and characterisation of the effects of a reference anti-androgen on the reproductive function based end-points in female fish.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation